Prophethood in Abrahamic Traditions: A Comparative Analysis - Nazir, Iymen (Pascasarjana IAIN Pontianak, 2025)
Abrahamic Religions—Judaism, Christianity, and Islam—are all prophetic religions. These religions share a common lineage of prophets with shared prophets. Prophets are the medium of communication between the divine and humanity. Although the faiths share the same lineage of prophets, starting with Adam, the description of the prophetic institution varies significantly in terms of the prophetic mission, authority, and finality. The paper aims to explore the prophetic mission of the Abrahamic religions, the link connecting them on a common platform, and the differences in the understanding of the prophethood in the three faiths. A systematic comparative framework is needed to explore shared roots and distinctive developments. The paper examines the concept of prophethood in the three faiths. It utilizes primary texts alongside secondary scholarship to identify the similarities and differences in the prophetic mission and its legacy, employing a comparative-theological approach. Judaism holds its roots in the teachings of Moses, Christianity in the teachings and resurrection of Jesus Christ, whereas Islam derives from the life and mission of the Prophet Muhammad. The three religions share a standard list of prophets with significant differences in the concept. It intends to evaluate and draw a comparison of the shared notions and differences between these faiths.